2022
DOI: 10.1364/boe.469380
|View full text |Cite
|
Sign up to set email alerts
|

In vivo monitoring of vascularization and oxygenation of tumor xenografts using optoacoustic microscopy and diffuse optical spectroscopy

Abstract: The research is devoted to comparison of the blood vessel structure and the oxygen state of three xenografts: SN-12C, HCT-116 and Colo320. Differences in the vessel formation and the level of oxygenation are revealed by optoacoustic (OA) microscopy and diffuse optical spectroscopy (DOS) respectively. The Colo320 tumor is characterized by the highest values of vessel size and fraction. DOS showed increased content of deoxyhemoglobin that led to reduction of saturation level for Colo320 as compared to other tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…These results correspond to Fujii et al who described the dynamics of tumor model oxygenation in the course of its growth with the electron paramagnetic resonance method [17]. Diffuse reflectance spectroscopy has been used as a method of experimental tumor oxygenation investigation and has demonstrated a certain decrease in StO 2 level and concentration of oxyhemoglobin, as well as an increase in deoxyhemoglobin content [18][19][20].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…These results correspond to Fujii et al who described the dynamics of tumor model oxygenation in the course of its growth with the electron paramagnetic resonance method [17]. Diffuse reflectance spectroscopy has been used as a method of experimental tumor oxygenation investigation and has demonstrated a certain decrease in StO 2 level and concentration of oxyhemoglobin, as well as an increase in deoxyhemoglobin content [18][19][20].…”
Section: Discussionsupporting
confidence: 85%
“…A temporal rise of blood oxygen saturation level in murine head and neck xenografts was shown in [21]. No changes in the oxygenation level of liver tumor and FSAII tumor models and HCT116 tumor model were demonstrated in [22] and [19] correspondingly. Fujii et al showed a gradual decrease in oxygenation of the SCC VII model due to the rise in oxygen consumption rate in the process of tumor growth [17].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…OA allows not only to see the features listed above, but also to visualize the appearance of new small vessels. Since SN-12C is a slow-growing tumor [24], we were able to trace the formation of zones with a network of new small vascular structures by day 11 of tumor growth, forming larger individual vessels, sprouting to the center of the tumor node by day 34 of growth and further, to the late stages of tumor growth, occupying the entire volume of the neoplasm.…”
Section: Resultsmentioning
confidence: 99%
“…At the moment, OAs is actively used in biological research and medicine to diagnose melanin-containing neoplasms, detect atherosclerotic changes in large blood vessels, and conduct neurobiological studies [16][17][18]. In oncology, several studies have already been carried out using OA imaging to diagnose superficial neoplasms [19][20][21], as well as to analyze vascular state of tumor models during growth and after treatment [22][23][24].…”
Section: Introductionmentioning
confidence: 99%